Bridging Fiqh and Positive Law: A New Paradigm for Child Legality and the Best Interest of the Child in Indonesia - Hanapi, Agustin; Aini, Sarina; Sari, Cut Endang Puspa (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This study aimed at explaining the shift in the legality of children in Indonesia in the decisions of the Religious Court and Syar’iyah Court regarding the determination of the origin of children. This normative legal research used a conceptual approach, legal regulations, and cases. The data were obtained from the decisions of the Religious Court and Syar’iyah Court as well as legal regulations in Indonesia. The data were collected through literature review. The research results showed that the judges’ considerations no longer strictly adhered to fiqh, but referred to Indonesian positive law and even ignored both by prioritizing justice and the benefit of children. The judges’ decisions that had accommodated the welfare of children were in line with maqāṣid al-sharī‘ah, which requires the maintenance of the five basic foundations for children such as religion, soul, reason, heredity, and property. This research confirmed that there has been a shift in the legality of children in Indonesia in judges’ decisions from fiqh to positive law which prioritizes the best interests of children.